PEREMPUAN DAN PANGGUNG DIALOG KEINDAHAN DUA SISI DUNIA PERAN - Rohman, Muh Fatoni (Studi Budaya Nusantara, 2019)
Abstract This article is about women's relations and the stage in performing arts. So far the relationship between the two has been read through internal readings that reveal the existence and dominance of gender. So in this paper, the external context is presented in analyzing the relationship between women and the performing arts stage. In this context, the process of reading relations between women and performing arts can be done by putting these two variables in the function of subjects and objects so that in this paper two reading perspectives are produced, namely: (a) The role of women in the stage, and (b) Functions stage for women. In the part of women's role on the stage can be seen in the analysis of female figures of performing arts (actress R.A. Srimulat and Tjijih) and women's functions in the performance stories (in the story of Sarip Tambak Oso). Whereas on the stage function for women, it can be seen that as a means of movement, the stage gives the same proportion between men. But as a means of expression, the stage provides more open space for women.